Intercellular communication in malignant pleural mesothelioma: properties of tunneling nanotubes - Ady, Justin W.; Desir, Snider; Thayanithy, Venugopal; Vogel, Rachel I.; Moreira, André L.; Downey, Robert J.; Fong, Yuman; Manova-Todorova, Katia; Moore, Malcolm A. S.; Lou, Emil (Frontiers in Physiology, 2014)
Malignant pleural mesothelioma is a particularly aggressive and locally invasive malignancy with a poor prognosis despite advances in understanding of cancer cell biology and development of new therapies. At the cellular level, cultured mesothelioma cells present a mesenchymal appearance and a strong capacity for local cellular invasion. One important but underexplored area of mesothelioma cell biology is intercellular communication. Our group has previously characterized in multiple histological subtypes of mesothelioma a unique cellular protrusion known as tunneling nanotubes (TnTs). TnTs are long, actin filament-based, narrow cytoplasmic extensions that are non-adherent when cultured in vitro and are capable of shuttling cellular cargo between connected cells. Our prior work confirmed the presence of nanotube structures in tumors resected from patients with human mesothelioma. In our current study, we quantified the number of TnTs/cell among various mesothelioma subtypes and normal mesothelial cells using confocal microscopic techniques. We also examined TnT length among adherent cells and cells in suspension. We further examined potential approaches to the in vivo study of TnTs in animal models of cancer. We have developed novel approaches to study TnTs in aggressive solid tumor malignancies and define fundamental characteristics of TnTs in malignant mesothelioma. There is mounting evidence that TnTs play an important role in intercellular communication in mesothelioma and thus merit further investigation of their role in vivo.